Yixintai treats chronic heart failure in rats by regulating gut microbiota and bile acid - Shi, Min; Yuan, Hui; Liu, Chengxin; Wei, Jiaming; Wang, Ziyan; Huang, Aisi; Zeng, Qinghua; Li, Ya; Guo, Zhihua (Frontiers in Microbiology, 2025)
IntroductionYixintai (YXT) medicine for chronic heart failure (CHF), has demonstrated safety and efficacy in the treatment of CHF. However, its precise mechanistic actions require further elucidation.MethodsThis study identified components in YXT using the UHPLC-QE-MS technique. A rat CHF model was created by ligating the left anterior descending coronary artery and an inflammatory injury model was induced in H9c2 cells using lipopolysaccharide (LPS) to evaluate the efficacy of YXT. After YXT treatment, changes in fecal gut microbiota and serum BAs profiles in rats were evaluated utilizing 16S rRNA sequencing and UHPLC-MS/MS techniques. Additionally, western blot (WB) and polymerase chain reaction (PCR) assays were conducted to assess the expression levels of TGR5 in both myocardial tissue and H9c2 cells. Cyclic adenosine monophosphate (cAMP), B-type natriuretic peptide (BNP), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) levels were also measured using enzyme-linked immunosorbent assay (ELISA).ResultsIn total, 1049 components were identified in YXT. YXT treatment effectively attenuated the inflammatory reaction, reduced serum BNP levels, alleviated the pathological changes in the colon and myocardium, and improved cardiac function in CHF rats. YXT treatment significantly improved gut microbiota diversity in CHF rats, enhancing beneficial bacterial populations and serum bile acid levels, while reducing the abundance of detrimental bacteria. Furthermore, YXT treatment enhanced TGR5 expression in the myocardial tissue and H9c2 cells of CHF rats.DiscussionThese findings suggest that YXT exerts its therapeutic benefits by reshaping the gut microbiota, modulating bile acid metabolism, and activating TGR5.